Suprasegmental features of CI children via classification of pre-linguistic utterances: two longitudinal case studies - Binos, Paris; Okalidou, Areti; Botinis, Antonis; Kyriafinis, Georgios; Vital, Victor (My University, 2013)
Background: The speech prosody of young children who have CIs has not been the subject of detailed investigation. This case study is a longitudinal investigation of the vocalizations of two young children with CIs. The aims were to examine the suprasegmental characteristics of the prelinguistic utterances of these CI children and to develop a method for deriving phonoprosodic classifications using acoustical and auditory analyses. Materials and methods: Spontaneous productions by two congenitally hearing-impaired Greek children fitted with a Nucleus-24 multichannel CI (ages 1: 10 and 2: 7; post-implant ages 0: 0 and 0: 6) were sampled for 6 months and, following transcription, classification of protophones was made. The analysis aimed to detect the frequency of occurrence of different protophone types in the infants’ utterances and to examine utterance duration and pitch contour via spectrography. Utterance characteristics were analyzed in relation to a) child’s age and b) post-implant age. Results: At post-implant age of 6 months, the younger and earlier implanted child showed more prelinguistic vocalizations and more complex structures than the older, later fitted child. The older, later CI recipient produced CV vocalizations at the beginning of implantation and gained a facility for frequent CV productions after 4 months of CI use. Conclusions: The findings are in agreement with other studies which observe that later CI recipients produce CV combinations at earlier phases of the prelexical period until the necessary auditory input is provided by CIs. Protophone vocalizations serve as a comparative parameter of speech production level in pre-lingual speech.
Keywords: Cochlear implants; Speech production; Speech therapy; Prosody; Deaf; Infants